Bacillus subtilis surface display technology: applications in bioprocessing and sustainable manufacturing - Howra Bahrulolum; Gholamreza Ahmadian (Biotechnology for Biofuels and Bioproducts)
Abstract The growing demand for sustainable and eco-friendly alternatives in bioprocessing, healthcare, and manufacturing has stimulated significant interest in Bacillus subtilis surface display technology. This innovative platform, leveraging both spore and vegetative cell forms, provides exceptional versatility for a wide spectrum of applications, spanning from green technologies to advanced biomedical innovations. The robustness of spores and the metabolic activity of vegetative cells enable efficient enzyme immobilization, biocatalysis, and biosensor development, facilitating bioremediation, pollutant degradation, and renewable energy generation. Additionally, B. subtilis surface display systems have demonstrated remarkable potential in vaccine development and drug delivery, offering a cost-effective, scalable, and environmentally sustainable alternative to traditional methods. These systems can effectively present antigens or therapeutic molecules, enabling targeted drug delivery and robust immune responses. This review explores recent advancements, challenges, and opportunities in harnessing B. subtilis surface display technology for sustainable biomanufacturing, green innovations, and transformative biomedical applications, emphasizing its role in addressing pressing global challenges in environmental sustainability and healthcare.